Inhaled Amikacin for Treatment of Refractory Pulmonary Nontuberculous Mycobacterial Disease - Olivier, Kenneth N. (2014)
National Institute of Allergy and Infectious Diseases. Laboratory of Clinical Infectious Diseases. Bethesda, MD, USA.